The Proof of the Early Months of Qamariyah between Science and Religious Commitment | إثبات أوائل الشهور القمرية بين الحملة العلمية والعودة إلى التعبد - Sofiyulloh Mukhlas (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2009)
This article discusses about the polemic among Muslim society in deciding firstdate of month of Qamariyah. Is it enough by ru’yah as well as mentioned in thetext of hadis or is it possible by hisab? That case becomes a serious matteramong Muslim society that needs to be discussed and solved, it relates to thecelebration of Idul Fitri and Idul Adha that could cause of performing salat ‘Id ontwo different days. The writer views, that both ru’yah and hisab can be used asreference in deciding first date of month of Qamariyah. The result is ru’yah askey to decide first date of month of Qamariyah as Rasulullah’s command, whilehisab is as a medium to see crescent such as telescope and other equipment.Finally, the writer confirms that there should be cooperation between Muslimjurisprudence and astronomer in order to get consensus and the unity ofMuslim society.